Anti-fascism as a determinant of Serbian national identity - Šuvaković, Uroš V. (Sociološki pregled, 2025)
The aim of this paper is to contribute to the understanding of the elements of Serbian national identity as the Serbs’ collective identity. It starts from understanding collective identities in which, apart from the consciousness of WE characterizing them, there is an important characteristic difference between social groups of the same kind, or the relation between WE and THEY. In that respect, it is argued that anti-fascism as a value is the characteristic of Serbian national identity that is insufficiently emphasized. Moreover, we do not determine anti-fascism primarily as an ideological matrix, but as the concretization of the value of libertarianism, about which the largest number of our authors dealing with this topic agree – that it is an element of Serbian national identity. A conclusion is drawn that anti-fascism as an element of Serbian national identity is also complementary with other national-identity characteristics of the Serbian people.
Keywords: collective identities; Serbian national identity; anti-fascism